UNE FAMILLE SANS CHEF EST-ELLE RÉELLEMENT POSSIBLE ? - Kouakou Konan Jérôme (European Scientific Journal, ESJ, 2014)
On November 21st, 2012, a new law on the marriage was voted in Côte d‘Ivoire. It corrects disparities between husband and wife by entrusting the responsibility for the family to the man and to the woman. In addition to this rebalancing of the roles wich was in discredit of the woman, the reform abolishes the concept of head of the family. This article questions this suppression in sight to reveal its utopian character. It shows, on the one hand, that this concept is not incompatible whith coadministration preached by the reform, and on the other hand, that leadership is consubstantial to any social organization, and that conséquently, it would be impertinent to think that the statute of head of the family can disappear indeed from the simple fact that it has been deleted from the law.